Is the Canadian Housing Market Overvalued? : A Post-crisis Assessment - Tsounta, Evridiki (IMF Working Papers; Working Paper ;, 2009)
Canadian house prices have increased significantly between 2003 and early 2008, with a marked downward trend since mid-2008, especially in the resource-rich western provinces. This paper estimates the evolution of equilibrium real home prices during this period in key provinces and finds that, following recent declines, home prices are now generally close to equilibrium throughout Canada. However, house prices in Alberta and British Columbia remain around 8 percent overvalued at the end of the sample (second quarter of 2009). Despite the limitations of econometric estimates of house-price dynamics, the measured small degree of overvaluation suggests that the Canadian housing market is essentially at equilibrium.